1990
DOI: 10.1210/jcem-70-1-89
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Endocrine Ophthalmopathy not Associated with Overt Thyroid Disease Have Multiple Thyroid Immunological Abnormalities*

Abstract: Twenty-two apparently euthyroid patients with endocrine ophthalmopathy not associated with goiter, antithyroid microsomal or antithyroglobulin antibodies, or overt thyroid disease (so-called ophthalmic Graves' disease) were tested for subclinical hyperthyroidism or hypothyroidism. We measured 131I uptake and scan, serum T3 (by RIA), and serum TSH using a sensitive (by immunoradiometric assay) assay. Three patients were found to be hyperthyroid, and 1 was hypothyroid. The remaining 18 patients, who remained eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 15 publications
(24 reference statements)
0
23
0
1
Order By: Relevance
“…Almost all the patients with euthyroid Graves' disease suspected ophthalmologically had abnormalities in thyroid function and/or in antithyroid auto-antibodies [26]. In combination with TRH test, T3-suppression test, TBII, TGHA and MCHA, we found abnormalities in the thyroid in 10 patients (77%), and more in 12 patients (92%) when TSAb was examined.…”
Section: Patients and Methods Statistical Methodsmentioning
confidence: 74%
“…Almost all the patients with euthyroid Graves' disease suspected ophthalmologically had abnormalities in thyroid function and/or in antithyroid auto-antibodies [26]. In combination with TRH test, T3-suppression test, TBII, TGHA and MCHA, we found abnormalities in the thyroid in 10 patients (77%), and more in 12 patients (92%) when TSAb was examined.…”
Section: Patients and Methods Statistical Methodsmentioning
confidence: 74%
“…Approximately 10% of patients with ophthalmopathy do not have hyperthyroidism. The majority of these patients have laboratory evidence of thyroid immune disease including antibodies to thyroid peroxidase or thyrotropin receptors (9). The negative test for thyroid-stimulating immunuglobulin in our patient made Graves' ophthalmopathy much less likely.…”
Section: Discussionmentioning
confidence: 67%
“…The onset of TAO is in most cases concomitant with the onset of hyperthyroidism, but TAO may precede or follow hyperthyroidism. 18 As the factors concerning the onset, severity, and drug responsiveness of TAO are yet uncertain and the role that hyperthyroidism management may play on TAO's emergence and development are also unclear, TAO management remains a key research topic. 19 In this review, we found therapeutic indication for TAO in 53 out of 167 patients.…”
Section: Discussionmentioning
confidence: 99%